Analisis Kepuasan Masyarakat dalam Pelayanan Kepala Desa Medan Estate Kecamatan Percut Sei Tuan - Andreas Roberto; Abdul Kadir; Nina Angelia (Universitas Medan Area, 2019)
The purpose of this study is to Analysis of Community Satisfaction with the Performance of Head Village in the Medan Estate. The Problems can be identified in this study are: 1) How the process of service in community to Performance’s Head of the Field in Percut Sei Tuan District Deli Serdang Regency. 2) What are the supporting and inhibiting factors in community service in the head office of Desa Medan Estate. Data Analysis used in this study is the Qualitative method for analyzing the data by describing the collected data who took the research location at the Office of the Head of the Medan Estate Village PercutSei Tuan Deli Serdang District. The data sources in this study were the community and the Head village. Data is collected based on interviews and documentation. The results of this study indicate that the analysis of community satisfaction in the Performance of the Village Head of Medan Estate, was reviewed from various interviews with the Medan Estate Village Community and village officials to increase community satisfaction with the performance of the Medan Estate Village Chief.